What claims best convey the quality of retailers' standard private label products? - Louis, Didier; Lombart, Cindy; Grappe, Cindy G.; Durif, Fabien; Florence, Charton-Vachet; Untilov, Olga (International journal of retail & distribution management, 2023)
PurposeConsumers consider retailers' standard private labels (PLs) as relevant choices, compared to national brands (NBs), and their demand for private label products has increased significantly over the past decade. At the same time, PLs have undergone a profound transformation as retailers have enhanced their quality. The goal of this research is to investigate the impact of claims used to highlight the enhanced quality of standard PL products on consumers' perceptions and behaviours.Design/methodology/approachA between-subjects experiment, set in a store laboratory, was used to study consumers' perceptions and behaviours. The impact of six non-nutrition claims – linked, according to the self-other trade-off, either to concern for consumers' health (internal to the self) or for the environment (external to the self) – on consumers' reactions has been studied. Then, the data collected were analysed with partial least squares structural equation modelling (PLS-SEM).FindingsThis research indicates that health claims retailers make to echo consumers' own concerns have positive impacts at three basic levels: the brand, the retail chain and the store. It also highlights the central role of trust in standard PLs, which, once activated by the non-nutrition claims made by retailers and the increase in the quality of standard PLs thus inferred by consumers, can improve consumers' attitude toward the food retailers' stores and reinforce their intentions to visit again and recommend them.Research limitations/implicationsFrom a theoretical perspective, this research supplements cue utilisation theory as it applies this framework to standard PLs and establishes that consumers use extrinsic cues (i.e. communications on non-nutrition claims) to infer the quality of standard PL brand products. It also complements scant studies on retailers' corporate social responsibility (CSR) with quality aspects of their own labels as it specifies the levers (i.e. the claims) to use to improve retailers' CSR image and consumers' behaviours.Practical implicationsFrom a managerial perspective, this research highlights the superiority of retailers' claims related to consumer health and, more specifically, of claims highlighting the natural origin of ingredients. For this specific assertion, trust in the standard PL and the CSR image of the brand have direct and indirect impacts, via attitude toward the stores, on consumers' intentions to return to and to recommend these stores.Originality/valueDespite the increasing importance of products as effective tools for communicating companies' CSR policies, scant research has been conducted on consumers' reactions to non-nutrition claims, which are increasingly prominent in the marketplace.